Subjectivity, culture and the datafication of music - Hesmondhalgh, David (Convergence (London, England), 2025)
The main objective of this article is to critique the notions of subjectivity, identity and selfhood underlying key approaches to the datafication of music, and some key normative positions associated with those approaches. I begin by showing how some of the most sophisticated and influential approaches to datafication of music (by Eric Drott and Robert Prey) draw on theorisation of the harms associated with datafication that depend upon the idea of ‘subjectification’. I then question this conception of subjectivity, tracing its origins in earlier modes of social theory. I argue that the emphasis on subjectification has resulted in approaches to digital identities, in studies of datafication in general as well as in culture and music, that focus on how technologies imply, construct or ‘demand’ certain ‘subject positions’ on the part of users. This approach, I claim, fails sufficiently to engage with the actual practices and lived experiences of users or audiences, and frames them in a way that downplays, neglects and even evacuates agency and autonomy as elements of subjectivity, identity and selfhood. I then argue that the normative basis of such subjectification critiques as applied to music is limited because those critiques depend on the limited conceptions of subjectivity, identity and selfhood characteristic of subjectification approaches in general. I also show that Drott and Prey’s accounts fall back on different groundings for critique than the subject formation theorising they purport to offer. These groundings are provided by two rather different theoretical concerns: political-economic critique regarding capitalist power and critiques of surveillance and privacy. I close by offering suggestions for better models of selfhood, identity and subjectivity that might inform a more integrated account of political-economic, socio-cultural and psychic domains. I also comment on the kinds of methodologies that might be entailed by adopting such models.